(untitled) (World Bulletin of Social Sciences, 2024)
This article recognizes an actual dual system of translation strategies which are classified as comprehension strategies and production strategies. However, the continues of the discussion regarding the latter and illustrates these production strategies in chapter with textual examples. The use of dictionaries during the textual production of a translation would therefore fall under the classification of semi-production strategies. In domain-specific cases, including official documents, the translator needs to recognise the consultation (in most cases just for confirmation) as an essential translation strategy definitely enhancing the final product. When reading a Japanese text, especially in the case of judicial matters, the translator needs to confirm if the lexical occurrence is regular or irregular with special readings and meanings. For irr stance, Japanese personal names, including family names, are very tricky in that the written representation in characters called “kanji” is not on a one-to-one basis. Instead, in Japanese one character can have multiple readings. With judicial matters, misreading a text and then mistranslating or misinterpreting it is of course a very serious matter that may lead to adverse consequences.